Environmental and management drivers of soybean yield in a subtropical region with recurrent drought and heat stress - Casali, Lucía; Herrera, Juan M.; Madias, Andres; Rubio, Gerardo (Frontiers in Agronomy, 2025)
Agricultural expansion in South America’s Semiarid and Subhumid Chaco has accelerated in recent decades, predominantly driven by the growth of soybean farming. Our objectives were to determine the main climatic and management constraints that explain soybean yields variability and to identify strategies to cope with them. Given the lack of locally validated best management practices, our approach was to analyze on-farm data from 2840 production paddocks with mixed models, attempting to capture the environmental and management heterogeneity of the area. The high variability in soybean yields in the study area was greatly determined by climatic variables. The predictors that explained the largest proportion of yield variance were the number of years with soybean as preceding crop, the effective rainfall between October (i.e. before planting) and April, the number of days with maximum temperatures above 35 °C between day 50 and 100 from planting and the mean maximum temperature between December and April. Fields that avoided soybean in recent rotations achieved higher water use efficiency, an effect further conditioned by rainfall. Based on our findings, the following agronomic strategies and research areas should be prioritized: i) increasing crop diversification and avoiding soybean monoculture; ii) implementing agricultural practices aimed to increase pre-plant water availability (i.e. maintaining high soil coverage); iii) sowing soybean at different dates within the same farm to expose the crops to varied climatic conditions